O efeito de mudanças drásticas no nível da água sobre a assembleia de peixes : o caso do rompimento da comporta em um reservatório Neotropical. - Baumgartner, Matheus Tenório (2016)
River damming, for reservoir formation, causes intense and dramatic changes that creates new environments, with particular structure and functioning. In these systems, flow control and artificial variations in water level are important determinants of the structure of fish assemblages. The objective of this study was to evaluate the effects of the rapid reservoir drawdown on the structure of fish assemblage in a Neotropical reservoir, in southern Brazil, operated by run-of-river. Water level variation was due to one of the spillway gates forfeiture, and caused the water level to vary up to 20 meters. A Canonical Analysis of Principal Coordinates (CAP) was used to summarize the structure of fish assemblage. Later, Spearman correlations were performed between each CAP axes and fish species abundances, to assess the species that most contributed to the observed patterns. The first two CAP axes identified strong spatial scales, while the third axis identified the time scale. The enhanced movement of individuals, coupled with reproductive stimulus were the most remarkable benefits of the reservoir refill. A noticeable negative effect was the loss of many fish that perished during the reservoir drawdown phase, addressed to adverse limnological conditions. Results showed significant benefits of water level variation on fish assemblage, and we suggest that, observed some peculiarities, this variation can be used for stable reservoirs management, as a tool to increase the abundance of fish species.